2014
DOI: 10.5380/avs.v19i2.34085
|View full text |Cite
|
Sign up to set email alerts
|

Padrão Biométrico, Medidas De Atrelagem E Índice De Carga De Equideos De Tração Urbana Do Município De Arapiraca, Alagoas

Abstract: RESUMO:Milhares de pessoas utilizam a carroça tracionada por equídeos como meio de trabalho ou suplementação de renda no âmbito mundial. Poucas são as pesquisas envolvendo a caracterização biométrica dos animais e as medidas dos equipamentos de atrelagem, buscando classificar os equídeos pela capacidade de tração, propondo discussões cientificamente embasadas acerca da capacidade de carga por animal, consequentemente diminuindo os maus tratos e dimensionando o trabalho de forma proporcional e coerente. Objetiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
6
2
0
Order By: Relevance
“…For adult donkeys, withers height (WH) was 131.1±5.5 cm (Table 3), falling well within the range established by the ABCJPÊGA (2016), which require a minimum WH of 120 cm for females. The findings of this study corroborate those of Brum (2010), who reported a mean value of 131 cm for male Pêga donkeys, but differ from those reported by Mariz et al (2014) and Pimentel et al (2014), who investigated the Nordestino breed of donkeys and reported WH values of 117 cm and 106 cm, respectively, indicating that Pêga donkeys are taller. These data also corroborate the findings of Oliveira (2004), who reported that the Pêga animals are larger when compared with other national breeds.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…For adult donkeys, withers height (WH) was 131.1±5.5 cm (Table 3), falling well within the range established by the ABCJPÊGA (2016), which require a minimum WH of 120 cm for females. The findings of this study corroborate those of Brum (2010), who reported a mean value of 131 cm for male Pêga donkeys, but differ from those reported by Mariz et al (2014) and Pimentel et al (2014), who investigated the Nordestino breed of donkeys and reported WH values of 117 cm and 106 cm, respectively, indicating that Pêga donkeys are taller. These data also corroborate the findings of Oliveira (2004), who reported that the Pêga animals are larger when compared with other national breeds.…”
Section: Discussionsupporting
confidence: 86%
“…In the analysis of morphometric indexes of adult female donkeys (Table 6), at the first evaluation of BI, it was confirmed that the animals could be classified as longilineal, similar to the observations recorded in other studies conducted on donkeys (Brum, 2010;Pimentel et al, 2014;Mariz et al, 2014;Folch and Jordana, 1997). Longilineal animals are morpho-functionally adapted to the racing activity, indicating the longer BL in relation to the thoracic depth, which thus provides greater speed (Cabral et al, 2004;McManus et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations